Low temperature activation of benzylic C-H bonds with heterogeneous Fe/MgO catalyst under atmospheric molecular oxygen - Cho, SH; Cheong, MS; Jung, KD; Kim, CS; Han, SH (ELSEVIER SCIENCE BV, 2004)
The room temperature benzylic oxidation was per-formed with Fe/MgO catalyst. This Fe/MgO catalyst was prepared by the dissolution-precipitation method. This heterogeneous catalyst, Fe/MgO, activated the C-H bond with atmospheric molecular oxygen even at 10degreesC; its catalytic activity was greatly enhanced by the addition of N-hydroxyphthalimide (NHPI) and/or acetaldehyde. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: N-HYDROXYPHTHALIMIDE NHPI; AEROBIC OXIDATION; COPPER-SALTS; ALDEHYDES; EFFICIENT; ALCOHOLS; ALKANES; COMPLEX; REDUCTION; ALKENES